Anticipating the motor anticipation: The cases of Lionel Messi and Andrea Pirlo - Giuriato, M.; Biino, V.; Zago, M.; Lovecchio, N. (European Journal of Sports & Exercise Science, 2019)
The suggestive hypothesis of the neural system of Messi that slows the external motor perception was recently proposed by Jafari and Smith and commented by Erren et al. This theory is re-discussed considering the principles of motor anticipation, fast decision making, the memory of past situations and originality during decision making. The anticipation of the motor anticipation was supposed as a distinctive characteristic of high-level players.